Electric field-induced two-step phase transformation and its contribution to the electromechanical strain in lead-free relaxor-based ceramics. Issue 8 (July 2023) - Yang, Hao; Zhao, Jinyan; Zhuang, Jian; Hinterstein, Manuel; Ren, Wei; Ye, Zuo-Guang; Zhang, Nan
Abstract: Sodium bismuth titanate-based solid solutions are important lead-free piezoelectrics with potential applications. Large electromechanical strain is of particular interest, which can be realized via the structural change in the relaxor states under an electric field. In this work, a polycrystalline ceramic 0.85Na1/2 Bi1/2 TiO3 –0.15BaZr0.2 Ti0.8 O3, in which a long-range ordered ferroelectric phase and a relaxor state coexist, has been investigated to unveil the origin of its electromechanical strain using various experimental techniques. An ergodic-relaxor to nonergodic-relaxor transition is first observed under a relatively weak electric field, and a more stable long-range ferroelectric phase is induced under a larger electric field. This two-step phase transformation is accompanied with the process of local polarization freezing as well as ferroelectric domain growth. The domain formation during the reversible phase transition is found to be the main contribution to the macroscopic strain. Our investigation provides an in-depth understanding of the origin of reversible electromechanical strain in the NBT-based relaxor-ferroelectric system.